From Morphology to Molecules: Advances in the Distinction of Multiple Primary Lung Cancers From Intrapulmonary Metastases in Non-Small Cell Lung Cancer - Olteanu, Gheorghe-Emilian; Kern, Izidor; Kalson, Lipika; Brcic, Luka (Advances in anatomic pathology, 2024)
The increasing incidence of multiple lung nodules underscores the need for precise differentiation between multiple primary lung cancers (MPLCs) and intrapulmonary metastases (IPMs). This distinction impacts patient prognosis and treatment strategies. The prevalence of multiple lung nodules, ranging from 19.7% to 55.5%, highlights the clinical significance of this challenge. Historically, the role of histopathology, particularly comprehensive histology assessment (CHA), has been pivotal in differentiating MPLCs and IPMs. However, CHA has significant limitations, resulting in a constant search for a better way to distinguish those lesions. The best strategy for delineating MPLCs from IPMs is a multidisciplinary approach combining clinical data, radiology, histology, and molecular methods. Histology provides architectural and cellular characteristics, radiology contributes anatomic context and lesion characterization, and molecular methods reveal molecular features critical for accurate differentiation. Incorporating clinical data further enhances diagnostic precision. This review presents current knowledge and current approaches to multiple lung tumors. It is clear that even with a combination of pathology, radiology, and molecular data, definitive classification of multifocal lung tumors is not always possible.